Enhancing women’s empowerment to reduce household poverty in rural Western China: social capital as a mediating pathway - Wang, Jing; Gu, Rui; Nie, Fengying; Dogot, Thomas (Frontiers in Sociology, 2025)
The pathway to household poverty reduction through women’s empowerment is critical for China’s rural revitalization. This study investigated the role of social capital in this process, using data from a household survey conducted in 2021 covering 1,239 dual-adult households in seven historically poverty-stricken counties across four provinces in rural China. We developed social capital indicators using proxy variables from our survey data and predicted the factor scores of the latent variable women’s empowerment. Subsequently, a causal mediation analysis was employed to detect both the direct and indirect effects of women’s empowerment on household poverty. The results have confirmed our hypotheses that women’s empowerment and social capital significantly reduce the probability of household poverty; women with higher empowerment scores are more likely to possess stronger social capital and social capital partially mediates the empowerment–poverty relationship. We concluded that policy-making that aims for sustainable poverty reduction in rural China should prioritize strategies that both strengthen women’s agency and enhance women’s social capital, particularly through structural enhancement measures to expand women’s engagement in cooperatives and associations, strengthen their representation in village governance, foster informal social networks, and invest in women’s education to enhance social capital and sustain poverty reduction in rural areas.